Challenge and Research Trends of Forecasting Financial Energy - Korol, Tomasz (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The measurement of economic entities' financial strength is one of the significant challenges of modern economic and financial research. With increased financial globalization, faster economic changes, and a new dimension of increased financial risk in the context of the COVID-19 pandemic crisis due to its biological nature and broad scope, affecting the whole world simultaneously, the issue of forecasting financial energy is gaining much more importance currently. This Special Issue entitled "Challenge and Research Trends of Forecasting Financial Energy" is devoted to the broad research area of forecasting financial energy of economic units such as enterprises, households, local governments, etc. Conceptualizing the term of financial energy, we aim to capture a wide spectrum of predicting and evaluating the financial standing, including various aspects of corporate finance, personal finance, and public finance.